Analisis Yuridis terhadap Pengaturan Sertipikat Elektronik (E- Sertipikat) atas Tanah Wakaf dalam Sistem Hukum Positif di Indonesia - Lyta Wury Rahmawati; Nourma Dewi; Yulian Dwi Nurwanti (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The digital transformation of land administration in Indonesia, including for waqf (endowment) land, has reached a significant milestone with the release of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (ATR/BPN) Number 1 of 2021 concerning Electronic Certificates. The purpose of this study is to offer a legal analysis of the rules pertaining to electronic certificates (E-certificates) for waqf land and its consequences for the preservation of waqf assets and legal certainty. Both statutory and conceptual methods were used in a normative legal approach. The results of the study show that there is a strong legal basis for the integration of Ecertificates for waqf land, which harmonizes electronic land rules with Law Number 41 of 2004 concerning Waqf. Although the system helps mitigate risks such as forgery, land disputes and physical document damage, its implementation still faces obstacles including limited digital infrastructure in remote areas, vulnerabilities during data migration and low digital literacy among. Nazhir (endowment administrators). Therefore, synergy between the Ministry of ATR/BPN and the Ministry of Religious Affairs, alongside continuous guidance for Nazhir, is essential to ensure legal certainty and the protection of waqf land in Indonesia.